The more grave delict against the Sixth Commandment of the Decalogue with a minor: some observations de lege lata and de lege ferenda - SKONIECZNY, PIOTR (Prawo Kanoniczne, 2017)
The Author comments on the constituent elements (objective, subjective and legal) of the offence specified in Art. 6 § 1 n. 1 SST/2010. He indicates the change in the aim of penal protection: from the celibate’s duty in can. 1395 § 2 CIC to mores in Art. 6 SST/2010. Following the canonical tradition, he calls for the extension to the lay Christian faithful of the element concerning the agent. He approves of the extended and theological meaning of the offence (‘the commission of the delict against the Sixth Commandment of the Decalogue’). The ecclesiastical legislator, however, has needlessly specified that a minor is someone below the age of eighteen years. In fact, this definition accords with the legal definition of a minor specified in can. 97 § 1 CIC. On the other hand, it would be a good idea to distinguish a paedophile sensu stricto from an ephebophile, and to determine the punishment accordingly. Moreover, according to the Author the habitu element is not justified in the case of the delict’s other kind of victim (‘habitually lacks the use of reason’). With reference to the subjective element, the Author notes the difference between the Latin code (the delict is only cum dolo) and the Eastern one (the delict can also be cum culpa), and the secular criminal codes with their so-called ‘eventual intention’ (dolus eventualis, e.g. the Polish criminal code). With regard to penal sanctions, the Author calls for a penalty latae sententiae, an impediment to ordination in the case of the paedophile sensu stricto, and the adaptation of can. 695 CIC to Art. 6 SST/2010. Finally, he suggests the abandonment of derogation from prescription, and the application of imprescriptibility to delicta graviora.